2009
DOI: 10.1590/s1806-37132009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Influência da massa magra corporal nas repercussões cardiopulmonares durante o teste de caminhada de seis minutos em pacientes com DPOC

Abstract: activities of daily living and is associated with lower survival in COPD patients.(2) Various etiologies, including sedentary lifestyle, hypoxemia, IntroductionWorldwide, COPD is one of the leading causes of death and physical incapacity.( AbstractObjective: Although lean body mass (LBM) has been associated with mortality in patients with COPD, its influence on functional limitation is not clear. The objective of this study was to analyze the cardiopulmonary variables in COPD patients with or without LBM depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In total, 13 study publications reported correlations between the SGRQ total score (SGRQ total ) and one or more exercise test outcomes ( Table 2 , Figure 2 ). 37 , 41 43 , 45 , 46 , 49 , 50 , 52 , 53 , 55 , 59 , 60 Of these, correlations between outcomes from the SGRQ total and distance covered in the 6MWT were most commonly reported. These correlations were typically significant, with six articles reporting weak negative Pearson’s correlations of −0.26, 37 −0.26 ( P <0.01), 59 −0.37 ( P <0.05), 41 −0.37 ( P =0.0228), 49 −0.39 ( P <0.01), 53 and −0.39 ( P =0.01), 60 demonstrating that as distance covered in the 6MWT increases, SGRQ total scores decrease, indicating better health status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 13 study publications reported correlations between the SGRQ total score (SGRQ total ) and one or more exercise test outcomes ( Table 2 , Figure 2 ). 37 , 41 43 , 45 , 46 , 49 , 50 , 52 , 53 , 55 , 59 , 60 Of these, correlations between outcomes from the SGRQ total and distance covered in the 6MWT were most commonly reported. These correlations were typically significant, with six articles reporting weak negative Pearson’s correlations of −0.26, 37 −0.26 ( P <0.01), 59 −0.37 ( P <0.05), 41 −0.37 ( P =0.0228), 49 −0.39 ( P <0.01), 53 and −0.39 ( P =0.01), 60 demonstrating that as distance covered in the 6MWT increases, SGRQ total scores decrease, indicating better health status.…”
Section: Resultsmentioning
confidence: 99%
“… 50 Three papers noted nonsignificant associations between the 6MWT and SGRQ total . 46 , 52 , 55 Limited data were available for other exercise tests, with moderate correlations given for the ISWT ( r =−0.55 45 , ρ =−0.55 43 ), weak–moderate correlations for the ICET ( r =−0.29 to −0.23, 37 , 41 ρ =−0.49 to −0.36, 50 depending on the outcome measure obtained [VO 2 or W max ]), and moderate Spearman’s correlations ( ρ =−0.54 50 and −0.58 43 ) for the ECET and TT, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to body composition, even though Pelegrino et al 15 stated that the reduced muscle mass is correlated to worse physical performance in relation to the presented fatigue, not being directly related to the reduced coursed distance in field tests, findings from other studies in literature showed up to 60% variation in the 12-minute walk test 16 , and positive significant correlation between muscle mass and the result of the 6-minute walk test 17 . With these findings, with our results we could confirm the correlation between muscle mass and the distance coursed also in ISWT, besides the correlation between pulmonary function and bone mass, which was not explored in that context in literature.…”
Section: Discussionmentioning
confidence: 94%
“…The circulatory response to a 50-meter walk in acute coronary syndrome was presented by Dias et al3 Furtado et al reported on blood pressure measurements during aerobic exercise in cardiac rehabilitation,4 whereas Oliveira et al reported on the effect of the walk test on the length of hospital stay for cardiac surgery patients 5. The relationships between fitness, waist circumference and hypertension in elderly Brazilian women were investigated by Krause et al6 Pelegrino et al studied the influence of lean body mass on cardiopulmonary repercussions during the six-minute walk test in patients with chronic obstructive pulmonary disease (COPD) 7…”
Section: Methodsmentioning
confidence: 99%
“…Ferreira et al analyzed respiratory rehabilitation in COPD in the transition from exercise training to real life 44. Pelegrino et al examined the influence of lean body mass on cardiopulmonary repercussions during the six-minute walk test in patients with COPD 7. Ziegler et al looked at predictors of oxygen desaturation during the six-minute walk test in patients with cystic fibrosis 45.…”
Section: Methodsmentioning
confidence: 99%